PENGARUH OBAT KUMUR YANG MENGANDUNG DAUN SIRIH TERHADAP pH PLAK PENGGUNA ORTHODONSI CEKAT DI KLINIK drg. DANI DAHLIUS, Sp. Ort YOGYAKARTA - Nadia Elfina; Suharyono Suharyono; Almujadi Almujadi (Journal of Oral Health Care, 2014)
Orthodontics treatment aims to improve the structure and function of teeth.Using a fixed appliance orthodontics potentially increase the risk of caries. low oralpH (pH 5.5) damage inorganic (mineral) email. pH ranges (6.1 to 7.7) yet email inorganicmaterial damage. Caries prevention can be done by gargling solution that reducesacidity and controlling oral plaque using mouthwash, which is made from naturalingredients that contains betel leaf. Betel leaf contains oil rich in chivakol, usefulas an antibacterial, with the power to kill bacteria five times that of antibacterial phenolgroup. This study aimed to determine the effect of mouthwash containing betel leafagainst plaque pH fixed orthodontics users. This experiment studies using a designone group pretest-posttest. Conducted in 2012. Location of research in dental clinicsdrg. Dani Dahlius, Sp.Ort Yogyakarta. Respondents study in which patients who comein the clinic and using fixed orthodontics for 1 year. At the time of the study before andafter rinsing with mouthwash betel leaf in size with a pH of plaque pH check. Analysisof test data using Wilcoxon with signifiicancy level = 0.05. Achieved average fixedorthodontics user plaque pH was 1,00 before and after the samples were treated bygargling mouthwash containing betel leaf changes mean that increasing plaque pH to3,63 with a margin (-2,63). statistical test user plaque pH fixed orthodontics, diiperolehz = -4,964. 0.002 and p value less than 0.05 significance level or P <0.05, whichmeans there is the influence of the use of mouthwash containing betel leaf againstplaque pH fixed orthodontics users.